Potential mechanisms linking poverty alleviation and health: an analysis of benefit spending among recipients of the U.S. earned income tax credit - Rita Hamad; Joseph Yeb; Kaitlyn Jackson; Wendi Gosliner; Lia C.H. Fernald (BMC, 2023)
Abstract Background The earned income tax credit (EITC) is the largest U.S. poverty alleviation program for low-income families, disbursed annually as a lump-sum tax refund. Despite its well-documented health impacts, the mechanisms through which the EITC affects health are not well understood. The objective of this analysis was to examine self-reported spending patterns of tax refunds among EITC recipients to clarify potential pathways through which income may affect health. Methods We first examined spending patterns among 2020-2021 Assessing California Communities' Experiences with Safety Net Supports (ACCESS) study participants (N = 241) and then stratified the analysis by key demographic subgroups. Results More than half of EITC recipients reported spending their tax refunds on bills and debt (52.3%), followed by 49.4% on housing, and 37.8% on vehicles. Only 3.3% reported spending on healthcare. (Note: respondents could list more than one possible spending category.) Participants ages 30 + were more likely to spend on bills and debt relative to those ages 18-29 (57.6% versus 39.4%, respectively). Other subgroup analyses did not yield significant findings. Conclusions Our findings suggest that EITC recipients primarily use their refunds on bills and debt, as well as on household and vehicle expenses. This supports the idea of the EITC as a safety net policy which addresses key social determinants of health.